2016
DOI: 10.3892/ol.2016.4303
|View full text |Cite
|
Sign up to set email alerts
|

c-MET inhibition enhances the response of the colorectal cancer cells to irradiation in vitro and in vivo

Abstract: Abstract. The aim of the present study was to investigate the effect of hepatocyte growth factor receptor (c-MET) inhibition on the viability of colon cancer cells and xenografts exposed to irradiation using short hairpin (sh)RNA or the c-MET inhibitor PHA665752. The underlying mechanisms were also investigated. Human colorectal adenocarcinoma HT-29 cells were infected with a lentivirus expressing shRNAs against c-MET and were irradiated at 0, 2, 4, 6 and 8 Gy. The viability of the cells was assessed by alamar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In this study, it has been discovered that in lymph node and liver metastasis groups, the positive rates of HGF and FAP were distinctly higher than those in non-metastasis groups. The ligand of c-MET is HGF that implicates c-MET in the development, progression and metastasis of cancer via acting on c-MET in tumor cells to activate downstream signaling pathway, and high c-MET expression has been detected in CRC which is associated with liver metastasis, suggesting that c-MET can be the potential marker of liver metastasis [23]. The up-regulation of HGF facilitates tumor cells invasion into lymph vessels, namely lymph node metastasis, via increasing the surface area of tumor cells on lymph vessels and giving new lymph vessel thinner wall, larger lumen and better permeability by inducing proliferation of lymphatic endothelial and lymph vessels directly or indirectly, which proves that HGF was in positive correlation with lymph node metastasis of CRC [24].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it has been discovered that in lymph node and liver metastasis groups, the positive rates of HGF and FAP were distinctly higher than those in non-metastasis groups. The ligand of c-MET is HGF that implicates c-MET in the development, progression and metastasis of cancer via acting on c-MET in tumor cells to activate downstream signaling pathway, and high c-MET expression has been detected in CRC which is associated with liver metastasis, suggesting that c-MET can be the potential marker of liver metastasis [23]. The up-regulation of HGF facilitates tumor cells invasion into lymph vessels, namely lymph node metastasis, via increasing the surface area of tumor cells on lymph vessels and giving new lymph vessel thinner wall, larger lumen and better permeability by inducing proliferation of lymphatic endothelial and lymph vessels directly or indirectly, which proves that HGF was in positive correlation with lymph node metastasis of CRC [24].…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, the development of c-met has been increasingly recognized to play pivotal roles in promoting tumor process. 22 24 Jia et al 25 found that inhibiting c-MET could enhance the response of the colorectal cancer cells to irradiation in vitro and in vivo. Our study proved that knocking down ITGA7 could enhance c-met.…”
Section: Discussionmentioning
confidence: 99%
“…Although others argued that the increase of MET in metastatic CRC was an acquired response to EGFR inhibition, not a de novo phenomenon ( 29 ), its prognostic value was confirmed by several independent researches ( 30 , 31 ). Moreover, suppressing MET by specific inhibitor or shRNA has a therapeutic role in CRC ( 32 , 33 ). CPM was less reported, and only one literature revealed that it was the target of miR-146a which promoted cell migration and invasion in CRC via CPM/src-FAK pathway ( 34 ).…”
Section: Discussionmentioning
confidence: 99%